COVID-19 pandemic and enrollment of critically Ill children in randomized clinical trials - Kandil, Sarah B.; Panisello-Manterola, David; Chegondi, Madhuradhar; Allen, Christine; Cholette, Jill M.; Kong, Michele; Pinto, Matthew; Schreiber, Hilary; Glau, Christie; Faustino, E. Vincent S. (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the association of the COVID-19 pandemic with enrollment rates of critically ill children in randomized clinical trials (RCT). We hypothesized that enrollment rates declined due to increased parental refusal.DesignCross-sectional analysis of 2 multicenter RCTs conducted pre- and post-COVID-19.SettingA total of 5 centers pre-COVID-19 and 15 centers post-COVID-19 conducting pediatric RCTs on enoxaparin prophylaxis against catheter-associated thrombosis.PatientsCritically ill children <18 years old with newly inserted central venous catheters.InterventionsRandomization to enoxaparin prophylaxis or usual care.MeasurementsEnrollment rates and reasons for non-enrollment were analyzed in 622 eligible children: 165 pre-COVID-19 (November 2017–August 2019) and 457 post-COVID-19 (May 2022–August 2024).Main resultsEnrollment rates declined from 30.9% pre-COVID-19 to 18.2% post-COVID-19 (P = 0.001). Reasons for non-enrollment differed significantly (P = 0.001). Parental unavailability decreased post-COVID-19 (17.7% vs. 34.2%, P < 0.001), while research staff unavailability increased (28.6% vs. 15.8%, P = 0.006). Overall parental refusal rates remained similar (38.6% pre-COVID-19 vs. 39.6% post-COVID-19, P = 0.85). However, among all eligible patients, enrollment failure due to parental refusal increased post-COVID-19 (64.1% vs. 46.3%, P = 0.003). Parental refusal inversely correlated with research staff availability (r = −0.71, P = 0.003).ConclusionsThe COVID-19 pandemic is associated with lower enrollment rates in RCTs enrolling critically ill children. Increased parental refusal post-pandemic is confounded by reduced research staff availability. Further investigation is needed to assess the role of science denialism and identify strategies to enhance enrollment in RCTs of critically ill children.